Stacked vs. Single Free Flaps in Autologous Breast Reconstruction: A National Analysis of Clinical Outcomes - Gupta, Nisha J; Ibrahim, Yasmine; Elkins, Emili; Romo Valenzuela, Alberto; Chervu, Nikhil; Mallick, Saad; Benharash, Peyman; Delong, Michael (Journal of Reconstructive Microsurgery)
Background Autologous breast reconstruction (ABR) is a reliable option for reconstruction after mastectomy. In cases where single donor sites do not offer adequate tissue, the use of “stacked” flaps, or multiple free flaps, can be brought together to provide optimal breast volume. This large-scale study aims to compare clinical outcomes, resource utilization and readmission rates between single and stacked flaps. Methods The National Readmission Database was used to retrospectively identify adult female patients who underwent ABR with free flaps between 2016 and 2020. In this study, free flaps were restricted to non-pedicled types, with latissimus dorsi (LD) and pedicled transverse rectus abdominis myocutaneous flaps (TRAM) excluded. Patients were categorized based on flap type (single vs. stacked) using relevant International Classification of Diseases Tenth Edition (ICD-10) procedure codes. Patient demographics, hospital factors, complication rates, and readmission data was analyzed. The primary outcome was difference in postoperative flap complication rates between single and stacked flaps. Results 52,180 adult females were included for analysis. Of these, 51,140 (n=98.5%) had single flaps and 783 patients (n=1.5%) had stacked flaps. Use of stacked flaps was not statistically associated with higher odds of any flap complication (AOR 1.16, p=0.46) compared to single flaps. Stacked flaps were associated with longer length of stay and higher hospitalization costs, but there was no significant difference in 30-day readmission compared to the single flap cohort. Conclusions Our study found similar rates of overall flap complications between the cohorts. Thus, in cases where more tissue is needed or desired, the use of stacked flaps appears to be a safe and feasible option to autologous breast reconstruction.